Analysis of the Application of Artificial Intelligence (AI) in Halal Product Supply Chain Management: A Systematic Literature Review - Julianti, Shofia Rizka; Agung Fatwanto (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2025)
The development of globalization has made digital technology play an important role in increasing the efficiency of supply chain management to ensure that its products are truly halal at the point of purchase for consumers. The technology that plays an active role in supply chain management is artificial intelligence (AI). This study aims to determine the effectiveness of implementing AI in halal product supply chain management. The object of this study is a scientific article that implements AI technology in halal product supply chain management with a qualitative approach through the Systematic Literature Review (SLR) method. Literature studies were conducted using Google Scholar and Science Direct to obtain detailed and up-to-date information on the topics to be studied. This study found 12 AI models that can be used in supply chain management. However, its implementation in the field of halal supply chains has not been widely implemented. This study also found that the implementation of AI in the halal product supply chain can improve operational efficiency and improve supply chain performance. However, successful adoption depends on technological readiness, good collaboration between technology and human expertise, and consumer trust. Investing in AI-based systems can significantly improve supply chain integrity and consumer trust.